1990
DOI: 10.1155/lc.11.49
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Excimer Pumped UV Laser Dyes I. p‐Terphenyls

Abstract: The performance characteristics of a series of new excimer pumped ultraviolet dyes are presented. Chemical structure modifications which influence dye performance are discussed. An evaluation of several alternative solvents shows that p-dioxane remains the solvent of choice based on dye performance. The influence of the cover gas in the dye circulator was examined and results are presented to show how dye performance can greatly depend on this factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Linear and recently reported cyclic oligo- p -phenyls with and without methyl and t -butyl substituents are among the simplest extended π -electron systems ( Chart 4 ). Linear oligo- p -phenyls have been utilized as luminophores in dye lasers and scintillators in near-UV and visible region for many years [ 76 , 77 , 78 ] due to their photochemically and thermally robust features. Although unsubstituted oligo- p -phenyls longer than five or six repeating units have limited solubility, p -dioxane is commonly used as a solvent for reasons not fully understood by the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Linear and recently reported cyclic oligo- p -phenyls with and without methyl and t -butyl substituents are among the simplest extended π -electron systems ( Chart 4 ). Linear oligo- p -phenyls have been utilized as luminophores in dye lasers and scintillators in near-UV and visible region for many years [ 76 , 77 , 78 ] due to their photochemically and thermally robust features. Although unsubstituted oligo- p -phenyls longer than five or six repeating units have limited solubility, p -dioxane is commonly used as a solvent for reasons not fully understood by the authors.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental apparatus and methods used in this study have been described in detail in the previous paper. 7 Although these dyes have been examined over a period of months, the dye lifetime and conversion efficiency data come from measurements done under identical operating conditions. For the sake of internal standardization on a day-to-day basis, the dye BBQ, 9 dye 14 in Table 1, inp-dioxane solvent was used as a benchmark.…”
Section: Methodsmentioning
confidence: 99%
“…We found a very similar result for the 4,4"-t-alkylsubstituted p-terphenyls. 7 Thus, it appears that ring substitution by tertiary alkyl groups produces the most long-lived oligophenylene laser dyes.…”
Section: General Properties Of Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the photoemission output could be increased further by adding two propyl groups to the methylene bridge. 23 The substitution of the terminal hydrogen atoms with alkoxy groups was generally found to red-shift the emission spectrum, 24 and for singly bridged molecules was also reported to enhance the photon to photon conversion efficiency of the dye. 25 Kauffman et al 23 found that the alkoxy substitution reduced the photostability of the compound, but Fleitz and co-workers 26 later reported that terminal tert-butyl substitution increases the stability.…”
Section: Introductionmentioning
confidence: 99%